Long-Term Tea Consumption Is Associated with Reduced Risk of Diabetic Retinopathy: A Cross-Sectional Survey among Elderly Chinese from Rural Communities - Cailian Xu; Mingchao Bi; Xuemei Jin; Manhui Zhu; Guohui Wang; Ping Zhao; Xiao Qin; Xun Xu; Xiaodong Sun; Na Ji; Jinxia Du; Jiaowen Xu; et al. (Journal of Diabetes Research)
Aim. To investigate the association between variables related to tea consumption (duration, frequency, and type) and the risk of diabetic retinopathy. Methods. A rural community-based, cross-sectional survey was conducted in Weitang Town, Suzhou, China. People aged 60 years or above were invited to complete the survey. All eligible patients underwent detailed eye examination. Diabetic retinopathy (DR) was diagnosed and graded based on the retinal fundus imaging. Diabetes was defined as fasting glucose concentrations of ≥7.0 mmol/L or self-reported diagnosis of diabetes. Information about tea consumption such as duration, type, and frequency, together with demographics and lifestyle characteristics, were collected using a face-to-face questionnaire interview. The association between tea consumption and the risk of DR was determined by univariate and multivariate logistic regression analyses. Results. Among the 5,281 participants, 614 had diabetes mellitus (prevalence of 11.63%). The prevalence rate of DR was 10.38% in the diabetic population and 1.04% in the general population. Compared with non-tea consumers, the crude OR values for DR in subjects with long-term and short-term tea consumption were 0.34 (95%CI=0.14‐0.82, p=0.016) and 1.64 (95%CI=0.74‐3.64, p=0.221), respectively. When adjusted for age, gender, and other confounders, consumption of tea for ≥20 years was associated with reduced odds of DR (OR=0.29, 95%CI=0.09‐0.97, p=0.044). Thus, long-term tea consumption was significantly associated with a lower risk of DR. There was no statistical significance between frequency or type of tea consumption with DR (p>0.05). Conclusion. Elderly diabetic Chinese residents who consumed tea for more than twenty years had a lower risk of DR compared to non-tea consumers. The long-term tea consumption may be an independent protective factor for DR. However, further studies are warranted to examine the association.